2006
DOI: 10.1073/pnas.0601139103
|View full text |Cite
|
Sign up to set email alerts
|

Production of knockout mice by random or targeted mutagenesis in spermatogonial stem cells

Abstract: Stem cells represent a unique population of cells with self-renewal capacity. Although they are important therapeutic targets, the genetic manipulation of tissue-specific stem cells has been limited, which complicates the study and practical application of these cells. Here, we demonstrate successful gene trapping and homologous recombination in spermatogonial stem cells. Cultured spermatogonial stem cells were transfected with gene trap or gene targeting vectors. Mutagenized stem cells were expanded clonally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 146 publications
(111 citation statements)
references
References 43 publications
2
109
0
Order By: Relevance
“…The numbers of spermatogonial stem-like cells that migrated to the seminiferous basal membrane and donor-derived colonies of spermatogenesis in each recipient testis were counted using a fluorescent microscope (30 seminiferous tubules were randomly selected). Because each colony was derived from a single SSC [19,24], we counted the donor-derived colonies of spermatogenesis from the 30 randomly selected seminiferous tubules and compared them in two different treatments. This provided a relative quantification of spermatogonial stem-like cell number in an injected cell suspension.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…The numbers of spermatogonial stem-like cells that migrated to the seminiferous basal membrane and donor-derived colonies of spermatogenesis in each recipient testis were counted using a fluorescent microscope (30 seminiferous tubules were randomly selected). Because each colony was derived from a single SSC [19,24], we counted the donor-derived colonies of spermatogenesis from the 30 randomly selected seminiferous tubules and compared them in two different treatments. This provided a relative quantification of spermatogonial stem-like cell number in an injected cell suspension.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…The cultured SSCs, termed germline stem (GS) cells or SSC lines, proliferated in a self-renewing manner for up to or beyond 2 years, while remaining stable genetically, epigenetically and karyotypically 10 . It has been reported that genetic modifications were feasible in GS cells 11,12 . Nonetheless, it has not yet been possible to induce spermatogenesis from these cells in vitro.…”
mentioning
confidence: 99%
“…The level of efficiency is five to ten times higher than that achieved by conventional methods using eggs or oocytes (Nagano et al 2001b). Moreover, the frequency of homologous recombination is comparable to that achieved in ES cells (Kanatsu-Shinohara et al 2006c). Thus, SSCs may be used as a vehicle for gene targeting.…”
Section: The Development Of a Long-term Culture System: Germ-line Stementioning
confidence: 60%
“…This is in contrast to ES cells, which often lose their germ cell potential due to trisomy (Liu et al 1997;Longo et al 1997). Similar to ES cells, GS cells can be used to produce transgenic and knockout animals via genetic transduction and drug selection (Kanatsu- Shinohara et al 2005aShinohara et al , 2006c. However, the efficiency of transgenesis is about 50%, which reflects the fact that the transgene is transmitted to half of the haploid cells.…”
Section: The Development Of a Long-term Culture System: Germ-line Stementioning
confidence: 99%